Progression of ultrasound plaque attenuation and low echogenicity associates with major adverse cardiovascular events. (3rd April 2020) - Shishikura, Daisuke; Kataoka, Yu; Di Giovanni, Giuseppe; Takata, Kohei; Scherer, Daniel J; Andrews, Jordan; Psaltis, Peter J; Puri, Rishi; Wolski, Kathy; Nissen, Steven E; Nicholls, Stephen J
Abstract: Aims: Intravascular ultrasound (IVUS) imaging can visualize vulnerable plaque features including attenuation (AP) and echolucency (ELP). While IVUS-derived vulnerable plaque features associate with microvascular obstruction during percutaneous coronary intervention, the relationship between these plaque features and clinical outcomes has not been established. This analysis aimed to evaluate the association of AP/ELP with cardiovascular events. Methods and results: Serial IVUS imaging was reviewed in 1497 patients, followed for 18–24 months, with coronary artery disease from two clinical trials. Attenuated plaque and ELP were identified to measure each characteristics (AP arc, ELP area, and lengths), which permitted calculation of an AP index (API) and ELP volume. Attenuated plaque/ELP progression was defined as patients with any increase of API or ELP volume on serial imaging. The major cardiovascular events (MACEs) were defined as death, myocardial infarction, stroke, and coronary revascularization. AP or ELP was identified in 282 patients (18.8%) at baseline and 160 (10.7%) patients demonstrated an increase in AP or ELP at follow-up. The incidence of MACE was higher in patients with baseline AP/ELP than those without (8.2% vs. 3.9%, P  = 0.002). Patients with AP/ELP progression were more likely to be acute coronary syndrome (41.9 vs. 33.2%, P  = 0.03) and have greater baseline percent atheroma volume (40.0% vs. 35.8%, P  < 0.001) than those without. On multivariable analysis, AP/ELP progression was more strongly associated with MACE [baseline AP/ELP: hazard ratio (HR) 1.76, 95% confidence interval (CI) 1.05–2.97, AP/ELP progression: HR 2.19, 95% CI 1.24–3.86]. Conclusion: Attenuation/ELP progression was associated with a higher prevalence of cardiovascular events, supporting a potential role for the identification of high-risk vulnerable plaques in patients with coronary artery disease.